Book Review: Islam and Human Rights - Chloryne Trie Isana Dewi (Faculty of Law, Universitas Padjadjaran, 2017)
Human rights and Islam are two very interesting issues to be discussed since there has been tension for decades. One agrees that Islamic law violates many aspects of human rights, yet other argues that human rights are against Islamic law. Nonetheless, there are also groups who accept that human rights and Islam are not contrary. This book written by Ann Elizabeth Mayer tries to give such objective perspective on the relation between human rights and Islam. With conspicuous title “Human Rights and Islam”, potential readers can assume that this book will discuss all matters in regards to the problematic of Islam and human rights in a whole. Beyond the expectation, this book focuses on the politics and tradition of Islamic countries in several ’attractive‘ areas such as Iran, Saudi Arabia, Afghanistan, Pakistan, and Sudan in interacting with human rights. However, Mayer declares from the very first sentence of the preface that this title is purposed for practical function for those who search for references on Islam and Human Rights and emphasizes that this book is written based on her research in the area of Middle East as her area of interest. Mayer argues that there is no Islamic consensus on a single Islamic human rights philosophy as her main thesis in this book. This claim is based on her research, that even other religions with long and complex traditions, they prone to create conflict in the interpretation between religious doctrine and human rights. Furthermore, she elaborates her research in 10 chapters of the book particularly on how Muslims from North Africa to Pakistan are responding human rights, from total rejection to wholehearted embrace. https://doi.org/10.22304/pjih.v4n3.a11